Treatment of primary full-thickness macular hole by intravitreal injection of expansile gas - Han, Ruoan (Eye (Lond), 2018)
OBJECTIVE: To evaluate the efficacy of intravitreal injection (IVI) of expansile gas to treat primary full-thickness macular hole (FTMH). METHODS: Prospective interventional case series. Twenty-six eyes of 26 patients in Peking Union Medical College Hospital with primary FTMH underwent IVI of perfluoropropane (C(3)F(8)) 0.2 ml, followed by 7–14 days’ face-down positioning. The macular hole closure rate, post-operative visual acuity, and the incidence of surgical complications were observed. The correlation between the patients’ age, macular hole diameter, pre-operative best-corrected visual acuity (BCVA), status of the vitreous, and the macular hole closure rates were analyzed. RESULTS: A total of 17 cases (65.4%) had hole closure after IVI of C(3)F(8) alone. The closure rate of small, medium, and large FTMH was 85.7, 80, and 33.3%, respectively. Pre-operative OCT examination showed that 10 cases (37%) had vitreomacular traction (VMT), and all of them achieved vitreous-macula separation after IVI of the gas. The diameters of the hole (P = 0.024) and the status of the vitreous (P = 0.038) had a significance difference for hole closure. The mean pre-operative and post-operative BCVA was 0.84 ± 0.29 and 0.49 ± 0.36 (logMAR), respectively (P < 0.01). One myope with persistent hole developed rhegmatogenous retinal detachment (RRD) 2 months after the surgery. Another myope with hole closure developed RRD 10 months after the surgery. They achieved hole closure and retinal reattachment after vitrectomy and scleral buckling, respectively. CONCLUSION: Intravitreal injection of C(3)F(8) gas alone was an effective treatment for small-sized and medium-sized primary FTMH, but further large prospective studies are needed.